Nurses’ Perspective about Evidence Based Nursing - Hassani, parkhideh, Khachian, alise, Khachian, alise (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim The complex and rapid changes in health care require using the best available evidences to have essential performance in caring. Considering nursing as an academic discipline, utilizing the results of research for improving nursing care and creating more satisfaction in patients is important so this study was designed to determine nurse’s perspectives about the concept of evidence based nursing. Materials and methods The approach of current study was descriptive phenomenology which was designed to study the perspective of nurses about the concept of evidence based nursing. Data collection method was semi structured interview and 7 participants were chosen by to purposive sampling. The study was conducted in Shahid Beheshti university affiliated hospitals and data were analyzed using Strubert’s phenomenological method. Findings The findings about evidence based nursing were codified in three main categories as improvement of quality of care evidences and values. In the case of second question about influencing factors two main categories as facilitating and interceptor factors were narrowed down. All indicated that knowledge of nurses about evidence based nursing is low therefore the utilization of research results as evidences were low also Conclusion Considering the findings of this study introducing the concept and utilization of research results should have patient’s higher satisfaction of received care. Keywords: Evidence based nursing, Evidences, Research utilization